Characterization and Comparison of Intestinal Bacterial Microbiomes of Euschistus heros and Piezodorus guildinii Collected in Brazil and the United States - Moro, Matheus Sartori; Wu, Xing; Wei, Wei; Mendes, Lucas William; Allen, Kerry Clint; Pinheiro, José Baldin; Clough, Steven J.; Zucchi, Maria Imaculada (Frontiers in Microbiology, 2021)
Background: Herbaceous insects are one of the main biological threats to crops. One such group of insects, stink bugs, do not eat large amounts of tissue when feeding on soybean, but are extremely damaging to the quality of the seed yield as they feed directly on green developing seeds leading to poorly marketable harvests. In addition to causing physical damage to the seed during feeding, the insects can also transmit microbial pathogens, leading to even greater yield loss. Conducting surveys of the insect intestinal microbiome can help identify possible pathogens, as well as detail what healthy stink bug digestive systems have in common. Methods: We used the conserved V4 region of the 16S rRNA gene to characterize the bacterial microbiome of the red-banded stink bug Piezodorus guildinii collected in Brazil and the United States, as well as the neotropical brown stink bug Euschistus heros collected in Brazil. Results: After quality filtering of the data, 192 samples were kept for analyses: 117 samples from P. guildinii covering three sites in Brazil and four sites in the US, and 75 samples for E. heros covering 10 sites in Brazil. The most interesting observations were that the diversity and abundance of some bacterial families were different in the different ecoregions of Brazil and the United States. Conclusions: Some families may be related to the better adaptation in some localities in providing nutrients, break down cellulose, detoxify phytochemicals, and degrade organic compounds, which makes it difficult to control these species.